Narapidana Narkotika Lanjut Usia: Sebuah Model Pembinaaan Lembaga Pemasyarakatan Khusus Narkotika - Hamja Hamja (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
The increasing population of elderly narcotics inmates in correctional institutions has given rise to important discourse to ensure the fulfillment of needs to support the process of improving behavior in correctional institutions. The Cirebon Class II A Special Narcotics Correctional Institution has implemented a number of behavior improvement and rehabilitation programs for the elderly which have had good success. This research uses a qualitative approach with data collection techniques in the form of interviews and observations. From this research it is known that the rehabilitation activities for elderly narcotics prisoners at the Class II A Cirebon Special Narcotics Correctional Institution are divided into two groups of activities, namely personality development and independence. By implementing these two programs, plus strong collaboration with P2HAM, the Cirebon Class II A Special Narcotics Correctional Institution is able to encourage successful rehabilitation of narcotics prisoners, especially the elderly group, so that it can be used as a model for other correctional institutions. Meningkatnya populasi narapidana narkotika lansia di dalam lembaga pemasyarakatan memunculkan wacana penting untuk memastikan pemenuhan kebutuhan dalam mendukung proses perbaikan perilaku di lembaga pemasyarakatan. Lembaga Pemasyarakatan Khusus Narkotika Kelas II A Cirebon mengimplementasikan sejumlah program perbaikan perilaku dan rehabilitas bagi lansia yang memiliki keberhasilan yang baik. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data berupa wawancara dan observasi. Dari penelitian ini diketahui bahwa kegiatan rehabilitas narapidana narkotika lansia di Lembaga Pemasyarakatan Khusus Narkotika Kelas II A Cirebon dibagi menjadi dua kelompok kegiatan yakni pembinaan kepribadian dan kemandirian. Dengan mengimplementasikan kedua program terebut, ditambah kolaborasi yang kuat bersama P2HAM, Lembaga Pemasyarakatan Khusus Narkotika Kelas II A Cirebon mampu mendorong keberhasilan rehabilitasi narapidana narkotika, khususnya pada kelompok lansia, sehingga dapat dijadikan sebagai percontohan bagi lembaga pemasyarakatan lainnya.